2013
DOI: 10.1108/ssmt-aug-2012-0018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison study of SAC405 and SAC405+0.1%Al lead free solders

Abstract: Purpose -The purpose of this paper is to study the effect of the addition of a small amount of Al (0.1 percent) on the properties of lead-free solder type Sn-4Ag-0.5Cu (SAC 405). Design/methodology/approach -The soldering properties of wettability and spreadability on a Cu substrate were studied, and the effect of Al on the growth of intermetallic compounds (IMCs) was observed. The shear strength of soldered joints was assessed. For comparison, soldering and strength tests were carried out on SAC 405 and SAC 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The microstructure gradually coarsened with the increase of Al in Figure 2. Reference [11] also reported that particle-shaped Bi phases were found distributed in Sn-rich phase matrix. Referring to the equilibrium Sn-Bi phase diagram [28], the reaction is L(liquid)→L + primary Sn →primary Sn + Bi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The microstructure gradually coarsened with the increase of Al in Figure 2. Reference [11] also reported that particle-shaped Bi phases were found distributed in Sn-rich phase matrix. Referring to the equilibrium Sn-Bi phase diagram [28], the reaction is L(liquid)→L + primary Sn →primary Sn + Bi.…”
Section: Resultsmentioning
confidence: 99%
“…The cost of Ag was high too. Furthermore, their liquidus temperature (around 217 °C) was higher than Sn-37Pb at 183 °C [11]. The easy oxidation of Sn-Zn alloys was a fatal weakness.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement was attributed to the interaction between Al and Cu at the solder/Cu interface. On the other hand, Kolenak et al [24] stated that the addition of 0.1 wt.% Al to the high-Ag-content Sn-4Ag-0.5Cu/Cu system slightly increased the wetting angle together with giving a slightly smaller spreading area due to the growth suppression of the Cu 6 Sn 5 IMC formed at the solder/Cu interface. Secondly, as Al is an active element, it is easier for it to accumulate at the solder/flux interface in the molten state, and subsequently, the interfacial surface energy is decreased.…”
Section: Methodsmentioning
confidence: 96%
“…Moreover, since the thickness of the IMC layer can be reduced by adding stabilizing elements such as Al [46] and nanoparticles such as CeO 2 [47] in the tin solder, future phase field simulations or calculations should consider building a multi-elements system coupling other alloying elements and additives to interpret mechanisms. Relative phase field simulation can shed light on the growth kinetics of interactions between alloying elements and IMCs, which cannot be achieved by experimental tools alone.…”
Section: Quantitative Prediction Of Growth Of Imcsmentioning
confidence: 99%